Intra - household social determinants of demand for maternal health Services in Mbarara district, Uganda - Nyakato, Viola Nilah (Mbarara University of Science and Technology, 2013)
This thesis examines intra-household social determinants of the use of maternal healthcare among in Mbarara District, Uganda. Effective use of antenatal care, skilled delivery and family planning are essential components of the Safe Motherhood Initiative and crucial for decreasing maternal mortality, yet many women in Uganda still find difficulties in accessing these services. Nationally, less than 6 in every 10 births are attended by skilled personnel and less than 5 in every 10 women attend the recommended four antenatal visits. In Uganda, the fertility rate is estimated at 6.2 children per women. Evidence shows that poor use of maternal healthcare has multiple manifestations which can be distinguished between those directly affected by actual accessibility and those indirectly affected through the indirect effects of household decision-making. This thesis examines the indirect determinants of use of maternal health care with a specific analysis of the effects of household division of labour, land decision-making and couple relations among households in Kashari County, Mbarara District. A cross sectional mixed methodology research design was used and data was collected using a survey questionnaire from 283 households, 7 individual interviews and 10 focus group discussions. In 2009, data was collected to assess how lower district level primary healthcare programmes integrate household level factors; 4 health workers and 6 community leaders were interviewed. In 2010, data was collected on household characteristics and use of maternal health services. The 2009/2010 study found significant gender inequalities in the division of labour, household labour, use and ownership of land and couple relations. A statistical analysis indicated that household labour is inversely associated with maternal healthcare use. Although land was found to be largely owned and controlled by men, it is an economic resource and a source of women’s daily occupation; it is on land that women spend more than 6 hours of their daily work. The study found that whereas at least 7 in every 10 women felt insecure on their family land, only 2 men in every 10 men shared such fears. Land use decision-making was found to significantly influence skilled birth attendance and ANC. The quality of couple relations was found to determine decision-making for the use of family planning and skilled care at birth, which was associated with men’s symbolic role as household heads. Husbands made 79% of income-related decisions and 73% of women said their husbands decide on their movements such as visiting friends. There was a significant level of poor couple communication whereby 15% of the respondents felt that they had never had open discussions with their spouses. In this study it was found that about 62% of women used skilled care during the last delivery and only 34% of women used contraceptives all the time. The study also found that family hierarchy limited women’s decision making and socially constrained maternal healthcare decision -making. Whereas the lower district health facilities are Primary Health Centres established to be sensitive to the social and economic needs of the community, the study hardly found an y practices that were directed towards dealing with household factors. Uganda’s lower district level healthcare system structures, though designed to support community engagement, follow Local Government administrative devolutions that do not deal effectively with intra-household living conditions.
Keywords: Intra - household; Maternal health services; Mbarara district, Uganda